2013
DOI: 10.1007/s13277-013-0793-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial D310 instability in Asian Indian breast cancer patients

Abstract: Somatic mutations in mitochondrial DNA (mtDNA) have been demonstrated in various tumors. Mitochondrial D-loop is a non-coding region in the mitochondrial genome, which has essential transcription and replication elements, and alterations in this region may affect both these processes. The D-loop has a poly-C tract (PCT) located between 303 and 315 nucleotides known as D310, which has been identified as a frequent hot spot mutation region in human neoplasia. In the present study, 77 pairs of breast tumor and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…Therein, we found that heterogeneity was the main character of the variations, especially the C-tract around positions 310 and 16189, which varied in length. These two variations were also detected in patients with breast cancer, lung cancer, and type 2 diabetes (Alhomidi et al, 2013;Chen et al, 2016). Our results confirmed the reliability of the two whole mtDNA genomes of the patients with colorectal cancer, which implied that our sequencing strategy could reduce the risk of artificial recombination efficiently (Fendt et al, 2009;Bi et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…Therein, we found that heterogeneity was the main character of the variations, especially the C-tract around positions 310 and 16189, which varied in length. These two variations were also detected in patients with breast cancer, lung cancer, and type 2 diabetes (Alhomidi et al, 2013;Chen et al, 2016). Our results confirmed the reliability of the two whole mtDNA genomes of the patients with colorectal cancer, which implied that our sequencing strategy could reduce the risk of artificial recombination efficiently (Fendt et al, 2009;Bi et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…In such cases, somatic mtDNA mutations may lead to selective transformation of breast epithelial cells and tumorigenesis. Various somatic mtDNA mutations have been detected in breast cancer [21, 23, 80, 81, 83, 85, 91, 101, 123–127], and here we will discuss a few of these mutations. It is important to note that the prevalence of germline mutations is significantly higher than that of somatic mutations, and most of the patients with germline mutations have multiple mutations [128].…”
Section: Somatic Mtdna Mutations and Risk For Breast Cancermentioning
confidence: 99%
“…These mutations have been detected with relatively higher frequency by comparison between the primary cancerous, matched para-cancerous normal, and distant normal tissues from the same patients (Brandon et al, 2006;Chatterjee et al, 2006). To date, a large number of somatic mutations have been detected among various kinds of tumor tissues, such as in breast cancer (Wang et al, 2007;Alhomidi et al, 2013), gastric cancer (Hung et al, 2010), esophageal squamous cell carcinoma (Kumimoto et al, 2004), lung cancer (Jin et al, 2007;Wang and Zhao, 2011;Fang et al, 2013;Yang Ai et al, 2013), and in aging individuals (Williams et al, 2013). Our previous study also revealed elevated somatic mutation rates through the examination of thirty entire mtDNA genomes from ten Chinese patients with lung cancer (Fang et al, 2013), as well as the poly-C repeat stretch (D310) of 79 patients (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%